National Structure And Number Of The Population Of Zarafshan District: Historical And Source Analysis - Yu.Kholkhujaeva (Genius Journals, 2022)
This article deals with the national composition, number and other characteristics of the population of Zarafshan district, which was a special administrative-territorial unit of the Governor-Generalship of Turkestan. To shed light on the problem, a historicalsource analysis of written sources, archival materials, research, and historical literature involved in the research process was conducted.
Keywords: ethnos; ethnic unity; primary written sources; oral survey; lords